Quality Analysis of Briquettes based on Waterding with Variation of Pressure and Pellet Geometry to Water Content and Value of Calories - Lintang Pratama; Dwi Pangga; Dwi Sabda Budi Prasetya (Universitas Pendidikan Mandalika, 2020)
This study is a research on water hyacinth-based briquettes which shows the calorific value of each form of briquettes. The purpose of this study was to analyze the quality of water hyacinth briquettes with variations in pressure and pellet geometry. The quality analyzed includes moisture content and calorific value. The method of making briquettes starts from charcoal, pounding, then mixing with tapioca starch adhesive. The composition of the mixture used is 90% water hyacinth charcoal with 10% tapioca starch adhesive. 4 geometric variations are used, namely, solid box, hollow box, solid tube and hollow tube with 3 pressure variations, namely, 10 PSI, 20 PSI and 30 PSI. Test results and analysis,briquettes at a pressure of 20 PSI produces a calorific value range of 91.15 - 150.14 cal / gram. The resulting calorific value is higher than the briquettes at a pressure of 10 PSI and 30 PSI with a heating value range of 93.84 - 148.79 cal / gram and 89.81 - 135.39 cal / gram. Hollow briquettes produce a calorific value range of 107.24 - 150.14 cal / gram higher than solid geometric briquettes which produce a heating value range of 89.81 - 148.79 cal / gram. So that the contribution of the results of this research is that the community makes briquettes with shape and pressure with good results shown in this study.